Effect of fiber orientation angle on patch repaired composite plates - Kaman, Mete Onur; Cetisli, Fatih (Walter de Gruyter Gmbh, 2021)
Stress intensity factors numerically investigated the Mode I loading of composite plates with an edge crack and repaired with a patch on a single side. The effect of the fiber orientation angle for both composite plate and the patch were analyzed with regard to crack length, adhesive properties, and plate thickness. The stress intensity factors were calculated by using the quarter point element that can be applied to 3D crack problems of homogeneous anisotropic materials.It was observed in this study that the fiber orientation angle affects the stress intensity factors significantly.
Keywords: Composite patch; stress intensity factor; finite element method; adhesive; orientation angle